The effects of job satisfaction, burnout and organizational culture on auditor's turnover intention / Norul Akma Mansor ... [et al.] - Mansor, Norul Akma; Othman, Rohana; Omar, Norliana; Mohd, Noor Saatila; Ab Rahman, Liyana (UiTM Cawangan Johor, 2018)
This study looks at the impacts of job satisfaction, burnout and organizational culture on auditor's turnover intention in public accounting firms. Job satisfaction has been classified as working environment, supervision and promotion while burnout is classified as emotional exhaustion, lack of personal accomplishment and depersonalization. For organizational culture, this factor has been further categorized into accomplishment/ innovation/ competence (AIC), cooperation/ supportiveness/ responsiveness (CSR) and emphasis on rewards (ER). A sum of 299 external auditors were chosen as the sample of the study. The multiple regression analysis results reveal that job satisfaction and burnout have significant effects on turnover intention while organizational culture does not have any critical association with turnover intention. While breaking down the factors by components, it was discovered that the working environment, promotion and ER are significant factors in clarifying the auditor's turnover intention. The findings of this study give imperative ramifications to both research and practice, especially for public accounting firms in tending to the issue of the high turnover rate among the auditors.